Numerical Study of Two-Phase Dusty Casson Fluid Flow over a Stretching Sheet with Aligned Magnetic Field and Newtonian Heating - Muhammad Shafirudin Fitri Saidis (Enhanced Knowledge in Sciences and Technology, 2024)
The purpose of this study is to investigate the behaviour of a dusty Casson fluid's boundary layer flow and heat transfer over a stretching sheet subjected to an aligned magnetic field and Newtonian heating. Similarity transformation technique is employed to convert the governing partial differential equations into a system of ordinary differential equations. The effects of key parameters, including the aligned magnetic field strength, Casson parameter, fluid-particle interaction parameter, Prandtl number, and conjugate parameter, are analyzed in detail. Key findings revealed that the aligned magnetic field and Casson parameter effectively reduced the fluid velocity but have minimal impact on the particle velocity.